Pelatihan Kewirausahaan dan Sistem Pemasaran Online kepada Pelaku UMKM Kecamatan Pakal, Kota Surabaya - Sitepu, Sri Nathasya Br; Sienatra, Krismi Budi; Teguh, Monika; Kenang, Irantha Hendrika (Universitas Nusantara PGRI Kediri, 2024)
Micro, small and medium enterprises (MSMEs) in Pakal District experienced a decrease in sales turnover after COVID 19. Consumers choose to shop online while MSME products are mostly sold conventionally. This resulted in a decrease in MSME turnover. The decrease in turnover can be overcome by holding entrepreneurship training and an online marketing system provided to MSME players in Pakal District, Surabaya City. The training method consists of simulation, mentoring and evaluation given to 20 MSME actors in Pakal District, Surabaya City. The results of entrepreneurship training 1) increased knowledge of entrepreneurial concepts, 2) internal and external analysis of business units (SWOT analysis) and choosing online marketing strategies were immediately carried out, 3) MSME actors managed business units based on the concept of 4 pillars of management, 4) MSME actors were able to innovate on marketing systems and products. Online marketing system training increases the capacity of MSME actors to market products online using social media (Facebook and WhatsApps). The end result of the online marketing system strategy is an increase in sales of MSME products.